Brain Gym Improves Concentration Learning to Read Children with Special Learning Difficulties - Diana Shanty; Budi Susetyo; Imas Diana Aprilia (INCLUSIVE EDUCATION, 2023)
Learning concentration is needed to complete school assignments, there are many things to stimulate children's concentration abilities. Therefore, it is necessary to develop programs that are in accordance with the abilities, conditions and learning needs of children, one of which is by practicing brain gymnastics. The purpose of this study was to determine the form of developing a brain gym program to improve the concentration ability to learn to read in children with specific learning difficulties. The method used in this research is a descriptive method with a qualitative approach. Data obtained through observation, interviews, semi-workshops and validation. The results showed that there were some children who had difficulty concentrating on learning to read, therefore the researchers collaborated with the teacher to develop a brain gym program which was then validated in two different schools. Researchers submit recommendations to teachers to implement the brain gym program that has been prepared.